(untitled) (المجلة الدولية للبحوث العلمية, 2026)
The sharp decline in oil prices in mid-2014 had profound and cumulative effects on the fiscal policies of many rentier states, with Iraq among the most severely affected. The reduction in oil revenues, coupled with the substantial costs of the war against ISIS, led to a significant federal budget deficit and placed the Iraqi economy under severe strain, resulting in a deep economic crisis. This crisis reflects Iraq’s rentier economic structure, as oil exports account for approximately 97% of total exports, diminishing the relative contribution of other sectors to GDP. In the absence of a clear policy to diversify revenue sources, the economy remains highly vulnerable to fluctuations in oil prices, deepening structural imbalances. To overcome the rentier trap, effective strategies are required to diversify revenue sources and establish a solid economic base insulated from the risks of volatile oil markets. At this stage, implementing value-added tax (VAT) measures and strengthening the role of the private sector in economic activities represent appropriate strategies for revenue diversification, while ensuring exemptions for essential goods to protect vulnerable groups. This research employs a descriptive-analytical approach to clarify the nature and significance of VAT, highlight the necessity of private sector participation in economic activities, and identify the key obstacles and components involved in diversifying Iraq’s economic base.